2018
DOI: 10.1177/0972652718777062
|View full text |Cite
|
Sign up to set email alerts
|

Do Domestic Sentiment and the Spillover of US Investor Sentiment Impact Mexican Stock Market Returns?

Abstract: We examine the relationship between sentiment and Mexican stock market returns. Results suggest a positive dynamic relationship between rational Mexican sentiment and equity market returns. Results also reveal a spillover of US sentiment on the return-generating process of the Mexican stock market that is distinct from domestic sentiment. This effect may be attributed to close economic ties and ease of capital flows between the two countries. Additionally, we find that rational sentiment and market returns are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Based on this study several similar studies have been conducted by other researchers, but there are differences ofopinion with the results obtained. Previous research on investor sentiment and market reaction or stock performance, namelyReference, [16][17][18][19] research shows that investor sentiment affects stock returns or market reactions in the stock market.Reference [10] suggested that the overconfidence of investors significantly affected the return of shares on the Tehran Stock Exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this study several similar studies have been conducted by other researchers, but there are differences ofopinion with the results obtained. Previous research on investor sentiment and market reaction or stock performance, namelyReference, [16][17][18][19] research shows that investor sentiment affects stock returns or market reactions in the stock market.Reference [10] suggested that the overconfidence of investors significantly affected the return of shares on the Tehran Stock Exchange.…”
Section: Introductionmentioning
confidence: 99%
“…This study finds a relationship between investor sentiment and exchange rate return and shows that investor sentiment has the ability to predict exchange rate returns. Using the VAR model, Perez-Liston et al (2018) come to the same conclusion. The authors find a negative relationship between the peso/US dollar exchange rate and investor sentiment.…”
Section: Related Research Overviewmentioning
confidence: 70%
“…The authors proved the determinant role of investor sentiment in forecasting future returns and volatility by the intense spillover of volatility from investor sentiment to returns. Perez-Liston et al (2018) find a significant relationship between sentiment and stock returns for the Mexican stock market in the period from January 1998 to December 2014. Also, using the VAR model, the authors address the spillover effect from US investor sentiment on Mexican stock market returns; and on Mexican sentiment.…”
Section: Related Research Overviewmentioning
confidence: 88%
“…Last but not least, Huang et al (2014) employed a combination of the wild-bootstrap technique and the mARM model of Amihud et al (2009) to address both problems. Finally, there are also a number of studies which did not focus on persistent regressors, small-sample bias, or the problem of overlapping periods at all -see, for example, Perez-liston et al (2018) and Concetto and Ravazzolo (2019) as the most recent examples. 22 Given the bootstrap simulation design (see Appendix B), it is not possible to make a proper inference about the return predictability of variables other than sentiment.…”
Section: Results Of the H-period Average Return Regressionsmentioning
confidence: 99%
“…To underline the degree of improvement achieved by combining several survey-based measures into one composite sentiment indicator, I decided to compare the out-of-sample capacity to predict future returns of the composite index sent with the capacity of the Consumer Confidence Indicator (CCI) calculated for Germany by DG ECFIN. The CCI was selected as the benchmark for the evaluation of forecasting performance because it is a popular proxy measure in academic circles and there are several studies that show that consumer confidence is a significant predictor of future stock market returns (Lemmon and Portniaguina, 2006;Schmeling, 2009;Chang et al, 2011;Corredor and Santamaria, 2015;Perez-liston et al, 2018). Prior to the analysis, the CCI measure was transformed to have a zero mean and unit variance.…”
Section: Comparison Of the Composite Survey-based Sentiment Indicatormentioning
confidence: 99%